2010
DOI: 10.1016/j.bbmt.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Trial Comparing Tacrolimus and Mycophenolate Mofetil to Tacrolimus and Methotrexate for Acute Graft-versus-Host Disease Prophylaxis

Abstract: Tacrolimus (Tac) plus methotrexate (MTX) is a standard regimen for graft-versus-host disease (GVHD) prophylaxis. Mycophenolate mofetil (MMF) is sometimes used instead of MTX to minimize toxicity, despite the lack of controlled studies demonstrating efficacy. We conducted a single-center, randomized phase II trial comparing Tac + MMF to Tac + MTX. Intent-to-treat analyses included 42 patients randomized to Tac + MMF and 47 to Tac + MTX. Patient characteristics were not different between the study arms. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 14 publications
5
83
0
3
Order By: Relevance
“…Among MTX/TAC-treated patients, we anticipated a grade II-IV acute GVHD rate of 80%, based on that observed in MTX/TAC-treated patients in a recent, prospective clinical trial at our center. 19 Based on previously published results of a single-arm phase II SIR/TAC trial results in which the incidence of grade II-IV acute GVHD was approximately 20% in comparison to previously reported incidence of 40-50% following MTX/TAC, 4,5 our a priori hypothesis was that we would observe a 50% reduction in this primary endpoint. The trial design included a concurrent comparator to facilitate interpretation, as there is variation in reported baseline incidences of grade II-IV acute GVHD between centers.…”
Section: Methodsmentioning
confidence: 99%
“…Among MTX/TAC-treated patients, we anticipated a grade II-IV acute GVHD rate of 80%, based on that observed in MTX/TAC-treated patients in a recent, prospective clinical trial at our center. 19 Based on previously published results of a single-arm phase II SIR/TAC trial results in which the incidence of grade II-IV acute GVHD was approximately 20% in comparison to previously reported incidence of 40-50% following MTX/TAC, 4,5 our a priori hypothesis was that we would observe a 50% reduction in this primary endpoint. The trial design included a concurrent comparator to facilitate interpretation, as there is variation in reported baseline incidences of grade II-IV acute GVHD between centers.…”
Section: Methodsmentioning
confidence: 99%
“…We subsequently reported on our experience with CSA and MMF compared to CSA and MTX in a retrospective analysis spanning from 1999 to 2007, again demonstrating reductions in mucositis, time to engraftment, length of stay, as well as risk of chronic GVHD, without difference in survival or relapse [14]. A study comparing Tac and MMF to Tac and MTX in both sibling and unrelated donor myeloablative HCT also demonstrated no difference in 100 day incidence of grade 2-4 GVHD, with a significant reduction in toxicities, but a higher incidence of grade 3-4 GVHD, primarily in unrelated donor transplants [15]. Additional small retrospective studies evaluating MMF in myeloablative transplant recipients have also confirmed improved toxicity and GVHD incidence and survival outcomes that are comparable to MTX [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…28 Given the randomized studies in adults demonstrating reduced mucositis when combining mycophenolate mofeteil (MMF) with CsA or tacrolimus rather than MTX, a question could be raised regarding the utility of maximizing strategies to enhance delivery of the full course of MTX. 29,30 However, the randomized trial with tacrolimus showed that MMF was less effective than MTX at reducing the risk of severe acute GVHD. 30 Furthermore, in vitro data demonstrate that MMF has substantially greater inhibition of natural killer cell proliferation and cytotoxic function than MTX, which may lead to a significant decrease in the GVL effect of natural killer cells.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, the randomized trial with tacrolimus showed that MMF was less effective than MTX at reducing the risk of severe acute GVHD. 30 Furthermore, in vitro data demonstrate that MMF has substantially greater inhibition of natural killer cell proliferation and cytotoxic function than MTX, which may lead to a significant decrease in the GVL effect of natural killer cells. 31,32 Our study was the first to assess the use of FA for MTX-related toxicity in pediatric allo-SCT patients receiving CSA and MTX for GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%